(untitled) (Malaysian Management Journal, 1997)
This article is concerned with the export market strategy adapted by manufacturers-exporters in resource- based industries. The characteristics, export performance and marketing strengths of firms adapting a market concentration strategy versus firms adapting a market diversification strategy are investigated. The results show that firms adopting a diversification strategy are larger, have more export experience and higher percentage of foreign equity participation, and achieved better export performance compared to firms adapting a market concentration strategy. The former also exhibits greater commitment to exporting and are significantly different from the latter as regards to sources of marketing competitive strengths.